Stability of Risk Preferences: Evidence from Laboratory Experiments - Tajima, Naoya; Kawagoe, Toshiji; Takizawa, Hirokazu (Journal of Behavioral Economics and Finance, 2025)
This study conducted laboratory experiments to examine the stability of preferences by investigating whether exogenous shocks, such as natural disasters, alter subjects’ risk preferences. Subjectss were exposed to exogenous shocks under conditions of risk, ambiguity, and unawareness. However, the mean value of the certainty equivalent did not change before and after the shocks in any of these conditions.